Sistem Monitoring Iklim Mikro pada Prototipe Greenhouse Tanaman Tomat menggunakan Metode Fuzzy dan Aplikasi Telegram - M. Ammar Batistuta Haryawan; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Microclimate is an environmental condition in a certain limit area. The greenhouse microclimate is the environmental conditions inside greenhouse which include temperature, humidity, and light intensity. Tomato plants require optimal temperature and humidity conditions in order to grow properly. Mamdani fuzzy logic is used to calculate the length of time the heater and cooler are on based on the parameters of temperature and humidity in the tomato greenhouse. Therefore, in this study a microclimate monitoring system will be created on a tomato greehouse prototype with the fuzzy method and telegram application. The system created uses the DHT22 sensor to read the temperature and humidity inside greenhouse. ESP32 is used as the main processor with support that can connect to the internet. Then the results of sensor readings and fuzzy calculation results will be displayed via the LCD as well as the Telegram application. The reading error on the DHT22 sensor is 4.7% for temperature and 4.5% for humidity. The fuzzy calculations performed by the system to determine the length of time the heater and cooler are in accordance with calculations in mathlab with the same input. The Telegram application has succeeded in sending notifications on the results of monitoring and fuzzy calculations with an average delay of 9.07 seconds.